2016
DOI: 10.1021/acscombsci.5b00186
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanistic Study on Ultrasound-Assisted, One-Pot Synthesis of Functionalized Benzimidazo[2,1-b]quinazolin-1(1H)-ones

Abstract: Ultrasound-assisted synthesis of benzimidazo[2,1-b]quinazolin-1(1H)-ones was achieved via piperidine-catalyzed three-component reaction of 2-aminobenzimidazoles, an aromatic aldehyde, and 1,3-dione in aqueous isopropanol. This mechanism was first suspected following our identification of unusual reaction intermediates in a one-pot reaction. An unprecedented coupling reaction, it involved a nucleophilic attack by 2-aminobenzimidazole on in situ generated Michael adduct, followed by electrocyclic ring formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Recently, the mechanistic studies on the multicomponent reactions was reported in literature under basic conditions that involve the nucleophilic attack of an amine on the in situ generated Michael adduct intermediate followed by six‐electron ring cyclization . It is contrary to the common belief of the accepted mechanistic route.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, the mechanistic studies on the multicomponent reactions was reported in literature under basic conditions that involve the nucleophilic attack of an amine on the in situ generated Michael adduct intermediate followed by six‐electron ring cyclization . It is contrary to the common belief of the accepted mechanistic route.…”
Section: Resultsmentioning
confidence: 98%
“…[45][46][47][48][49] Among different metal oxides, ZnO nanoparticles have been widely used as an efficient environmentally friendly catalyst due to its high catalytic activities and reactivity in various organic transformations. [50][51][52][53] In connection with these findings, and in continuation of our work on multicomponent reactions [54][55][56][57][58][59][60][61][62][63] as well as on the synthesis of multi-armed molecules, [64][65][66][67][68][69][70] we report herein the synthesis of novel poly(tetrahydrobenzo [4,5]imidazo[2,1-b]quinazolinones) linked to a benzene or methane core via phenoxymethyl or benzoyloxy spacers.…”
mentioning
confidence: 87%
“…Fused heterocyclic compounds containing nitrogen are frequently investigated for their wide range of biological activities that are not shown in each homonuclear scaffold. Among them, tetrahydrobenzo [4,5]imidazo [2,1-b]quinazolinones have received considerable attention because of their reported pharmacological applications. [1][2][3][4][5][6] Moreover, multicomponent reactions (MCRs) have recently gained a new dimension in the field of organic synthesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations